«ҒӘРИП-АШЫҚ» ДӘСТАНЫНЫҢ ХАЛЫҚ БАҚСЫЛАРЫНАН ЖАЗЫП АЛЫНЫЎЫ ҲӘМ БАСПАДА БАСЫП ШЫҒАРЫЛЫЎЫ - Есебаев, М.М. (FAN va JAMIYAT, 2025)
Throughout their historical journey, the Karakalpak people have created numerous artistic folk oral works, passing them down from generation to generation, orally, through teachers and students, and in written book form. This article discusses the recording, collection, and publication of the "Garib-oshiq" epic, inherited from our ancestors and passed down from the mouths of the people and storytellers. This is one of the most important issues in modern folklore studies.